Successful Bullying Prevention Programs: Influence of Research Design, Implementation Features, and Program Components - Hahn Fox, Bryanna; Farrington, David P.; Ttofi, Maria M. (International Journal of Conflict and Violence (IJCV), 2012)
Bullying prevention programs have been shown to be generally effective in reducing bullying and victimization. However, the effects are relatively small in randomized experiments and greater in quasi-experimental and age-cohort designs. Programs that are more intensive and of longer duration (for both children and teachers) are more effective, as are programs containing more components. Several program components are associated with large effect sizes, including parent training or meetings and teacher training. These results should inform the design and evaluation of anti-bullying programs in the future, and a system of accreditation of effective programs.